A study on solution chemistry and crystallization behavior of L-alanine in the presence of additives / Muhamad Fitri Othman - Othman, Muhamad Fitri (2013)
Crystallization is one of important purification process especially in pharmaceutical industries. However, the presence of impurities in the solution is known to cause a profound effect on the final crystal product. Increasing the level of understanding on the effect of additives to the solution crystallization is important. It is the objective of this thesis to investigate the effect of additives on the solution chemistry and the produced crystals. The ability of incorporation of additive on the surface morphology was also assessed through computational technique. The solubility experiment of L-alanine, with L-leucine and glycine as additives to the L-alanine solution were carried out by using isothermal method. Prediction of L-alanine crystal morphology and the likelihood of additives incorporation on selective site of the crystal surface via molecular modelling are also presented. The binary system and ternary systems were found to deviate from the ideal system by negative deviations representing a high solute-solvent interaction. Meanwhile, the results from PXRD and DSC analyses indicate that there is an interaction between additives molecules and host crystal surface through adsorption mechanism and thus promotes the formation of a solid solution. The simulated morphology and the calculated lattice energy reveal small deviation from the experimental data. Thus, Dreiding potential function and Mulliken atomic change are the most suitable set to be used to predict the morphology of L-alanine. Modelling studies of additives incorporation on the L-alanine crystal reveal that both additives have different propensity to incorporate on the selective facet of L-alanine.